2D Euler elastica in constrained environments - Stavole, Martina; Sato Martin de Almagro, Rodrigo; Capobianco, Giuseppe; Brüls, Olivier; Leyendecker, Sigrid (conference, HFSS International Conference on Highly Flexible Slender Structures (THREAD annual meeting), 2023)

A generalized-alpha scheme for the simulation of flexible multibody systems with constraints - Harsch, Jonas; Capobianco, Giuseppe; Eugster, Simon R.; Leine, Remco I. (conference, 92nd GAMM Annual Meeting, 2022)

A geometric view on the kinematics of finite dimensional mechanical systems - Winandy, Tom; Capobianco, Giuseppe; Eugster, Simon R. (Proc. Appl. Math. Mech. (PAMM), 2018)

A Moreau-type variational integrator - Capobianco, Giuseppe; Eugster, Simon R. (Proc. Appl. Math. Mech. (PAMM), 2016)

An augmented Lagrangian formulation of the planar elastica in constrained environments - Stavole, Martina; Sato Martin de Almagro, Rodrigo; Capobianco, Giuseppe; Brüls, Olivier; Leyendecker, Sigrid (conference, 7th IMSD International Conference on Multibody System Dynamics, 2024)

An extended version of the Intermediate Axis Theorem for a freely rotating rigid body - Leine, Remco I.; Capobianco, Giuseppe (Proc. Appl. Math. Mech. (PAMM), 2021)

A nonsmooth generalized-alpha method for mechanical systems with frictional contact - Capobianco, Giuseppe; Harsch, Jonas; Eugster, Simon R.; Leine, Remco I. (International Journal for Numerical Methods in Engineering, 2021)

A nonsmooth RATTLE algorithm for mechanical systems with frictional unilateral constraints - Breuling, Jonas; Capobianco, Giuseppe; Eugster, Simon R.; Leine, Remco I. (Nonlinear Analysis: Hybrid Systems, 2024)
In 1983, Andersen proposed the RATTLE algorithm as an extension of the SHAKE algorithm. The RATTLE algorithm is a well-established method for simulating mechanical systems with perfect bilateral constraints. This paper further extends RATTLE for simulating nonsmooth mechanical systems with frictional unilateral constraints (i.e. frictional contact). With that, it satisfies the need for higher-order integration methods within the framework of nonsmooth contact dynamics in phases where the contact status does not change (i.e. no collisions/constant sliding states). In particular, the proposed method can simulate impact-free motions, such as persistent frictional contact, with second-order accurate positions and velocities and prohibits penetration by unilateral constraints on position level.<br

A RATTLE integrator for the simulation of unilaterally constrained mechanical systems - Capobianco, Giuseppe; Breuling, Jonas; Leyendecker, Sigrid (conference, GAMM Annual Meeting, 2024)

A rockfall simulation scheme which preserves the stability properties of rotating rocks - Capobianco, Giuseppe; Leine, Remco; Bartelt, Perry; Lu, Guang (conference, ENOC 2020 10th European Nonlinear Dynamics Conference, 2022)

Comparison of Moreau-type integrators based on the time finite element discretization of the virtual action - Capobianco, Giuseppe; Winandy, Tom; Eugster, Simon R.; Leine, Remco I. (9th European Nonlinear Dynamics Conference, 2017)

Dynamic simulation of the Wilberforce pendulum using constrained spatial nonlinear beam finite elements - Harsch, Jonas; Capobianco, Giuseppe; Eugster, Simon R. (Proc. Appl. Math. Mech. (PAMM), 2021)

Dynamics of finite-dimensional mechanical systems on Galilean manifolds - Capobianco, Giuseppe; Winandy, Tom; Eugster, Simon R. (Proc. Appl. Math. Mech. (PAMM), 2019)

Dynamics of flexible multibody systems with frictional contact - Capobianco, Giuseppe (poster, GAMM Annual Meeting, 2023)

Event-capturing Lobatto-type integrators for mechanical systems with frictional contact - Capobianco, Giuseppe (conference, European Network for Nonsmooth Dynamics (ENNSD) Symposium, 2023)

Event-capturing simulation of nonsmooth systems - Capobianco, Giuseppe; Breuling, Jonas; Leyendecker, Sigrid (poster, GAMM Annual Meeting, 2024)

Exergetic port-Hamiltonian systems for multibody dynamics - Lohmayer, Markus; Capobianco, Giuseppe; Leyendecker, Sigrid (Multibody System Dynamics, 2024)
Multibody dynamics simulation plays an important role in various fields, including mechanical engineering, robotics, and biomechanics. Setting up computational models however becomes increasingly challenging as systems grow in size and complexity. Especially the consistent combination of models across different physical domains still requires significant effort. This motivates the study of formal languages that enable a compositional approach to modeling multiphysical systems with basic guarantees. The paper shows how multibody systems, or more precisely assemblies of rigid bodies connected by lower kinematic pairs, can be described as Exergetic Port-Hamiltonian Systems (EPHS). The EPHS modeling language features a straightforward graphical syntax for expressing the energy-based interconnection of hierarchically nested subsystems. This reduces cognitive load and facilitates clearer communication among experts, nonexperts, and computational tools. Hierarchical nesting of systems enables abstraction of lower-level details and promotes the reuse of models at different levels of complexity. At the lowest level, there are three basic kinds of systems, representing energy storage and reversible/irreversible energy exchange. The structured approach guarantees fundamental properties of macroscopic systems, such as conservation of energy and nonnegative entropy production. In combination with the compositional syntax, this makes building and modifying models simpler and less error-prone.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Compositionality; Modeling language; Multibody systems; Multiphysics; Rigid body dynamics; Thermodynamic consistency; Variational principle

Finite element formulations for constrained spatial nonlinear beam theories - Harsch, Jonas; Capobianco, Giuseppe; Eugster, Simon R. (Mathematics and Mechanics of Solids, 2021)

Geometric description of time-dependent finite-dimensional mechanical systems - Eugster, Simon R.; Capobianco, Giuseppe; Winandy, Tom (Mathematics and Mechanics of Solids, 2020)

Introduction to Numerics (INUMS) - Capobianco, Giuseppe; Huang, Dengpeng; Sato Martin de Almagro, Rodrigo; Leyendecker, Sigrid (invited lecture, FRASCAL Mini Lecture, 2022)

Kinematics of finite-dimensional mechanical systems on Galilean manifolds - Winandy, Tom; Eugster, Simon R.; Capobianco, Giuseppe (Proc. Appl. Math. Mech. (PAMM), 2019)

Lobatto-type variational integrators for mechanical systems with frictional contact - Capobianco, Giuseppe; Harsch, Jonas; Leyendecker, Sigrid (Computer Methods in Applied Mechanics and Engineering, 2023)
his paper introduces a family of Lobatto IIIA-IIIB methods for simulating mechanical systems with frictional contact. These methods extend the existing schemes by addressing both bilateral and unilateral constraints, as well as set-valued Coulomb friction. The Lobatto IIIA-IIIB methods presented in this paper make a substantial contribution to the ongoing endeavor of developing event-capturing versions of high-order schemes. By stating a generalized version of the principle of virtual action for nonsmooth mechanical systems, the integrators are derived from an appropriate discretization of it. The discrete contact laws are found by discretizing the impenetrabilty condition as well as the Newton-type frictional impact laws in an event-capturing way. The presented discrete contact laws exhibit no contact penetration and satisfy the involved unilateral constraints both on position and on velocity level. This behavior is showcased using benchmark example

Mechanical systems with frictional contact: Geometric theory and numerical simulation - Capobianco, Giuseppe (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
This dissertation deals with the mathematical description and the simulation of mechanical systems with frictional contact. First, a geometric theory for the description of smooth mechanical systems is developed, which is then extended to allow for nonsmooth motions, i.e., motions with discontinuous velocities. The developed nonsmooth theory of mechanics is used to describe mechanical systems with frictional contact. Finally, two numerical schemes for the simulation of such systems are derived by using a time finite element method and the generalized-alpha approach, respectively.<br

Modeling planar pantographic sheets using a nonlinear Euler-Bernoulli beam element based on B-spline functions - Capobianco, Giuseppe; Winandy, Tom; Eugster, Simon R. (Proc. Appl. Math. Mech. (PAMM), 2018)

Moreau-type integrators based on the time finite element discretization of the virtual action - Capobianco, Giuseppe; Eugster, Simon R.; Leine, Remco I. (Proc. Appl. Math. Mech. (PAMM), 2017)

Nonsmooth Lobatto-type variational integrators based on the discretization of the virtual action - Capobianco, Giuseppe; Breuling, Jonas; Leyendecker, Sigrid (conference, ENOC European Nonlinear Dynamics Conference, 2024)

On different geometric approaches to the dynamics of finite-dimensional mechanical systems - Eugster, Simon R.; Capobianco, Giuseppe; Winandy, Tom (Proc. Appl. Math. Mech. (PAMM), 2019)

On the divergence theorem for submanifolds of Euclidean vector spaces within the theory of second-gradient continua - Capobianco, Giuseppe; Eugster, Simon R. (Zeitschrift für Angewandte Mathematik und Physik, 2022)

Rattle for mechanical systems with frictional unilateral constraints - Harsch, Jonas; Capobianco, Giuseppe; Eberhardt, Lisa; Eugster, Simon R.; Leine, Remco I. (conference, ICCM 2023 International Conference on Composite Materials, 2023)

Recent progress on the EPHS modeling language: Multibody systems and discrete-time semantics - Lohmayer, Markus; Lynch, Owen; Capobianco, Giuseppe; Leyendecker, Sigrid (conference, 2nd Brig Workshop on Dissipativity in Systems and Control, 2024)

Simulating mechanical systems with frictional contact using a nonsmooth generalized-alpha method - Capobianco, Giuseppe; Harsch, Jonas; Eugster, Simon R.; Leine, Remco I. (Proc. Appl. Math. Mech. (PAMM), 2021)

Soft pneumatic actuator model based on a pressure-dependent spatial nonlinear rod theory - Eugster, Simon R.; Harsch, Jonas; Bartholdt, Max; Herrmann, Marco; Wiese, Mats; Capobianco, Giuseppe (poster, ICRA 2022, IEEE International Conference on Robotics and Automation, 2022)

Soft Pneumatic Actuator Model Based on a Pressure-Dependent Spatial Nonlinear Rod Theory - Eugster, Simon R.; Harsch, Jonas; Bartholdt, Max; Herrmann, Marco; Capobianco, Giuseppe (IEEE journal of robotics and automation, 2022)
To describe the mechanical behavior of a soft pneumatic actuator, we present a nonlinear rod theory, which recognizes the chamber pressurization as contribution to the resultant contact forces and couples. Accordingly, the pressure actuation can be considered as part of the rod’s constitutive laws, which relate the contact interactions with the rod’s kinematics and the chamber pressures. The theory allows for nonlinear constitutive laws, which are capable of describing strengthening or softening behavior of largely deformable materials. The theory was applied to a three-chamber actuator to predict its centerline as well as the cross-section orientations in static equilibrium. The resulting governing equations were spatially discretized using beam finite elements. We evaluated four different actuator models that are contained in the presented theory regarding describability and predictability of the end effector position. Existing rod models with linear elastic material laws can describe the tip-displacement with an averaged deviation of 9.1 mm in the training set and 11.4 mm in the test set. With a deviation of 2.8 mm and 4.9 mm in the training and test set, respectively, the most enhanced model, for which the pressure chamber radii increase with increasing pressure, is more than 2 times more accurate.<br

Stability of rigid body motion through an extended intermediate axis theorem: application to rockfall simulation - Leine, Remco I.; Capobianco, Giuseppe; Bartelt, Perry; Christen, Marc; Caviezel, Andrin (Multibody System Dynamics, 2021)

The GAMM Juniors - Warkentin, Andreas; Schussnig, Richard; Capobianco, Giuseppe; Kikis, Georgia (2024)
The group of GAMM Juniors consists of early-career scientists who represent the younger generation within the Association of Applied Mathematics and Mechanics (GAMM). This article provides an overview of the organization and activities of the GAMM Juniors. In particular, we share experiences, report on recent developments, and highlight potential opportunities.<br
Keywords: GAMM; GAMM Juniors; Young Academics

The principle of virtual work and Hamilton's principle on Galilean manifolds - Capobianco, Giuseppe; Winandy, Tom; Eugster, Simon R. (Journal of Geometric Mechanics, 2021)

Time finite element based Moreau-type integrators - Capobianco, Giuseppe; Eugster, Simon R. (International Journal for Numerical Methods in Engineering, 2018)